Diagnostic accuracy of shear wave elastography versus laboratory parameters as non-invasive screening tool for esophageal varices - Khaled Mohamed Ali Shehata; Abdul-Allah Ismael Kelany; Salma Mokhtar Osman Hassan; Ramy Mohamed Ahmed; Peter Atef Mounir; Amira Hassan AbdelAziz (SpringerOpen, 2024)
Abstract Background Variceal hemorrhage from the rupture of esophageal varices is accompanied by a substantial mortality rate. So, newly diagnosed cirrhotic patients are recommended to perform screening esophago-gastroduodenoscopy (EGD) for identifying varices. The primary objective of the present research was to ascertain the most precise biochemical and ultrasonographic variables that have the potential to non-invasively forewarn the occurrence of varices in cirrhotic patients. The study evaluated different parameters such as aspartate aminotransferase-to-platelet ratio index (APRI), platelet count/splenic diameter (PC/SD), portal vein velocity (PVV), and splenic and hepatic stiffness in prediction of EV. Methods This is a cross-sectional study that was conducted on 100 cirrhotic patients based on clinical, laboratory, and radiological assessments. All patients were subjected to thorough clinical examinations; laboratory tests were conducted to assess liver function and calculate Child-Pugh score and non-invasive tests for detecting esophageal varices such as APRI, PC/SD, Doppler ultrasonography for assessment of PV Doppler, and hepatic and splenic elastography. All patients got an endoscopic assessment in order to examine and classify the esophageal varices. Results Based on the current study, we found that predictors for EV among the studied patients were the following: PC/SD ratio with odds ratio (OR) was 2.20, PVV with OR was 4.68, liver stiffness with OR was 1.99, and splenic stiffness with OR was 3.55. With ROC curve analysis, PVV has the best overall accuracy (85.4%) for prediction of EV with an area under the curve of 0.79 at cutoff point < 7.09 (cm/s) followed by splenic stiffness that has 82.6% overall accuracy with an area under the curve of 0.71 at cutoff point > 62.22 kPa. Conclusion PVV and splenic stiffness measurement hold potential as non-invasive markers for predicting the presence of esophageal varices in individuals with liver cirrhosis. Moreover, these markers can also aid in predicting the occurrence of advanced esophageal varices.